Beiträge zur Insektenfauna der DDR: Hymenoptera: Sphecidae. 1. Nachtrag. - Jacobs, Hans-Joachim; Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1990)
Since Oehlke’s description of the Sphecidae was published in 1970, numerous changes in taxonomy and nomenclature habe occurred. The present supplementary paper is based on that work and gives 13 modified keys. Many new data on systematics, literature, biology and faunistics are added. Three species are new, so that now 204 species have been established. The results are based chiefly on recent collecting, for a smaller part on the evaluation of old collections.